2014
DOI: 10.1155/2014/972897
|View full text |Cite
|
Sign up to set email alerts
|

Preoxidation and Activation of the Lignin Char: Carbonization and Oxidation Procedures

Abstract: A comprehensive process of pretreatment and oxidation of lignin char was developed to optimize the production of activated carbon. The lignin char was obtained by carbonization of lignin under nitrogen at 600°C for 2 hours. The optimum time and temperature used to oxidize the char without destruction were, respectively, 6 hours and 245°C. The oxygen improves the reactivity of the sample in CO2and evolved the sample of a thermoplastic behaviour to a thermosetting behaviour. The oxygenation in air of the lignin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(56 reference statements)
2
2
0
Order By: Relevance
“…Various chemical activators, such as KOH 10 , HCl, HNO 3 and H 3 PO 4 were utilized, along with temperatures ranging from 500 to 900 °C 60 . The surface area of the produced lignin‐based activated carbon was found to be between 86 and 1509 m 2 /g 9,61 . The results within the scope of the present study were found to be similar.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Various chemical activators, such as KOH 10 , HCl, HNO 3 and H 3 PO 4 were utilized, along with temperatures ranging from 500 to 900 °C 60 . The surface area of the produced lignin‐based activated carbon was found to be between 86 and 1509 m 2 /g 9,61 . The results within the scope of the present study were found to be similar.…”
Section: Resultssupporting
confidence: 65%
“…60 The surface area of the produced lignin-based activated carbon was found to be between 86 and 1509 m 2 /g. 9,61 The results within the scope of the present study were found to be similar.…”
Section: Samplessupporting
confidence: 79%
“…Duration of pre-treatment is 6 hours and pre-oxidation temperature is 245°C. Choice of the duration and the aforementioned temperature has been the subject of previous work [4]. The sample obtained under these conditions is called CL600 (245°C,6h,air).…”
Section: Procedures Of Pre-oxidationmentioning
confidence: 99%
“…Sun et al [9] activated corn straw lignin via a one-step activation with H 3 PO 4 for 120 min and at an activation temperature from 300 to 600 • C. They found that the highest surface area and pore volume were obtained at 500 • C (820 m 2 g −1 and 0.8 cm 3 g −1 , respectively). Slow pyrolysis of a commercial lignin powder was carried out at 600 • C for 2 h and the resulting char was physically activated with CO 2 [10]. They obtained a specific area of nearly 394 m 2 g −1 when activating at 700 • C for 1 h and, by performing a partial oxidation on the char prior to activation, they increased this value up to nearly 530 m 2 g −1 .…”
Section: Introductionmentioning
confidence: 99%